Adaptation of Artificial Intelligence Literacy Scale into Turkish: A Sample of Pre-Service Teachers - Uğraş, Hilal; Merve,; Ugras, Mustafa (My University, 2024)
This study aims to adapt the Al-LS translated by Wang et al. (2022) into Turkish and create a scale suitable for assessing the AI-L of pre-service teachers. The study used the survey method within the scope of the quantitative method. The sample of the study consisted of 440 pre-service teachers (pre-school and primary pre-service teachers) from a state university in the Eastern Anatolia Region of Turkey. The original scale consists of 12 items, 4 factors, and a 5-point Likert-type structure. In the first stage, we conducted translation studies to assess the language validity of the adapted scale. Then, the data collected from the part of the sample determined for EFA (Exploratory Factor Analysis) were analyzed. The results show that the adapted scale preserves the original scale structure. The data collected from the part of the sample designated for CFA (Confirmatory Factor Analysis) was also analyzed. The results of the analysis show that the scale has acceptable and good-fit indices. In terms of reliability, Cronbach’s Alpha reliability coefficients show that the scale has a reliable structure. The results of the analysis indicate that the scale adapted to Turkish has a valid and reliable structure.
Keywords: Artificial intelligence; scale adaptation; Al literacy; artificial intelligence literacy (AI-L)